Analysis of the Use of Instagram Social Media in Increasing the Positive Image of PT Maharupa Gatra - Asep Supriatna; Amun; Bani Mahardhika; Oki Wahyudi; Wulan Furrie Lenggana (Formosa Journal of Sustainable Research, 2023)
The purpose of this writing is for analyzing the use of Instagram social media in improving positive image of PT Maharupa Gatra. This research aimed to analyze the obstacles and solution conducted to overcome the public relations obstacle in improving positive image of PT Maharupa Gatra. The method of this research was using descriptive qualitative method. Data collecting techniques were using observation, deep interview, literature study both printed and online. The result of this research shows that the public relations in PT Maharupa Gatra is using Instagram social media as a device to publish the company to the public by informing through social media the promotional program in PT Maharupa Gatra by making interesting content in order to make interaction with the consumers and followers on Instagram social media of PT Maharupa Gatra. By using Instagram social media, the company became easier in informing every information aimed for the customers and became more cost saving in the promotion, because promoting using social media can be more saving than using conventional media. So far, everything conducted by PT Maharupa Gatra in improving positive image to the public using Instagram social media is very precise in the digitization era nowadays, and making the public relations to be able to innovating in improving the positive image in PT Maharupa Gatra